Differential expression of the angiotensin-(1-12)/chymase axis in human atrial tissue. (August 2015) - Nagata, Sayaka; Varagic, Jasmina; Kon, Neal D.; Wang, Hao; Groban, Leanne; Simington, Stephen W.; Ahmad, Sarfaraz; Dell'Italia, Louis J.; VonCannon, Jessica L.; Deal, Dwight; Ferrario, Carlos M.
Objective: Heart chymase rather than angiotensin converting enzyme has higher specificity for angiotensin (Ang) I conversion into Ang II in humans. A new pathway for direct cardiac Ang II generation has been revealed through the demonstration that Ang-(1-12) is cleaved by chymase to generate Ang II directly. We address here whether Ang-(1-12) and chymase gene expression and activity are detected in the atrial appendages of 44 patients (10 females) undergoing heart surgery for the correction of valvular heart disease, resistant atrial fibrillation or ischemic heart disease. Methods and results: Immunoreactive Ang-(1-12) expression was 54% higher in left atrial compared with right atrial appendages. This was associated with higher abundance of left atrial appendage chymase gene transcripts and chymase activity, but no differences in angiotensinogen mRNA. Atrial chymase enzymatic activity was highly correlated with left atrial but not right atrial enlargement as determined by echocardiography, while both tyrosine hydroxylase and neuropeptide Y atrial appendage mRNAs correlated with atrial angiotensinogen mRNAs. Conclusions: Higher Ang-(1-12) expression and upregulation of chymase gene transcripts and enzymatic activity from the atrial appendages connected to the enlarged left versus right atrial chambers of subjects with left heart disease defines a role of this alternate Ang II forming pathway in the processes accompanying adverse atrial and ventricular remodeling.